PENINGKATAN PENGUASAAN KOSAKATA BAHASA ARAB MELALUI PENGGUNAAN MEDIA WORD WALL - Azizah, Hanifah Nur (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2018)
Application of the word wall  method is one of alternative to improve students Arabic vocabulary. A problem for student of class III A in MI Al-Ba’ats is the low of Arabic vocabulary which has an impact on the students learning outcomes. The aim of this skills research are to improve of students Arabic vocabulary skills by using  word wall media. This research used the Classroom Action Research (CAR) with fourth cycles. Each cycles concisted of six phases, which: identification of problems, need assessment, idea, implication, and decision making. The subject of the research are 21 students of the class III A MI Al-Ba’ats. The data sources of the research are the research and students. Data collection techniques are used an observation, an interview, tests and documentation. If the individual completeness reaches ≥ 65 and if value of the whole completeness reaches 75% of the students more than ≥ 65, then it could he said as a complete learning outcomes. The average value of learning outcomes in the pre-action is 62 and the value of the whole completeness is 33.3%. The average value of learning outcomes in the first cycle 69 and the value of the whole completeness is 66.7%. The average value of learning outcomes in the second cycle is 73 and the value of the whole completeness is 85.7%. The average value of learning outcomes in the third cycle is 80 and the value of the whole completeness is 95.2%. The average value of learning outcomes in the fourth cycle is 80.1 and the value of the whole completeness is 95.2%. The conclution of this research is by using word wall media, it can improve students Arabic vocabulary skills at class III A of MI Al-Ba’ats.